تجارت کے قرآنی اصول: تفا سیر احکام القرآن کی روشنی میں: Quranic Principles of trading in the light of Tafseer Ahkam al-Qur’an - Syed Noor Ul Hasan (MEI, 2023)
Islam is a complete code of conduct and way of life, which has provided complete teachings on every aspect of life including beliefs, society, worship, ethics and affairs. In the Holy Qur'an, guidance has been given in all the fields of life. Among all, the financial matters remain the most important subject matter of the Holy Qur'an. So, while the Qur'an has emphasized on worship and duties, it has also given importance to seeking livelihood and earning halal income. It is obligatory and necessary for a Muslim to earn halal sustenance and try to avoid haraam sustenance. Obtaining halal sustenance is possible only when a person obtains it in accordance with the prescribed methods of Shariah. Allah Almighty has also made trade a means of meeting the economic needs of human beings. If trade is done in a lawful and halal manner, then the profit earned from it will also be considered halal. If trade is done in illegal and haraam ways, then Profits from this will also be considered haraam. The issues related to finance and trade has been given much importance in the Holy Quran. Because these matters are directly related to human beings. If there is any ambiguity or thirst in them, there is a danger of corruption on earth. Therefore, it was necessary to explain in detail the rules and instructions in this regard. Therefore, the Qur'an al-Hakim has given detailed injunctions on this subject. Among the financial matters mentioned by the Qur'an, the emphasis is on trade, widows and their types, prohibitions and permissions related to them. The Qur'an has given clear instructions on commercial matters. Judgments on some of these matters have been given in-principle instructions while the details of some of them have been given by the Holy Prophet (SWS) by explaining the verses related to them. Here our focus will be on the Qur'anic principles, teachings and decrees regarding trade which Allah Almighty has mentioned in the Qur'an Al-Hakim with reference to trade, as well as the verses and commentaries given by the jurists and commentators belonging to different schools of jurisprudence. It will also be reviewed in detail.